2020
DOI: 10.1016/j.bmc.2020.115326
|View full text |Cite
|
Sign up to set email alerts
|

Hi-JAK-ing the ubiquitin system: The design and physicochemical optimisation of JAK PROTACs

Abstract: PROTACs have recently emerged as a novel paradigm in drug discovery. They can hijack existing biological machinery to selectively degrade proteins of interest, in a catalytic fashion. Here we describe the design, optimisation and biological activity of a set of novel PROTACs targeting the Janus kinase family (JAK1, JAK2, JAK3 and TYK2) of proximal membrane-bound proteins. The JAK family proteins display membrane localisation by virtue of their association with cytoplasmic tails of cytokine receptors and there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 35 publications
0
49
0
Order By: Relevance
“…Recently, an increasing number of publications have emerged where the physical properties of PROTACs are accounted for in their design, or in the rationalisation of their efficacy [121][122][123][124]. Mares et al [125], developed a potent cIAP-recruiting PROTAC (82) for the degradation of RIPK2 containing a PEG linker (pDC 50 = 9.4 in THP-1 monocytes, Figure 17).…”
Section: Deg S _mentioning
confidence: 99%
“…Recently, an increasing number of publications have emerged where the physical properties of PROTACs are accounted for in their design, or in the rationalisation of their efficacy [121][122][123][124]. Mares et al [125], developed a potent cIAP-recruiting PROTAC (82) for the degradation of RIPK2 containing a PEG linker (pDC 50 = 9.4 in THP-1 monocytes, Figure 17).…”
Section: Deg S _mentioning
confidence: 99%
“…In this way, the transfer of ubiquitin units within the ternary complex can lead to potent target degradation through the ubiquitin-proteasome system. Polyethylene glycol (PEG) chains are the most common type of linkers used so far due to their polarity and flexible nature (Bondeson et al, 2018;Pettersson and Crews, 2019;Sun et al, 2019), but other examples include pure lipophilic alkyl chains (Winter et al, 2015;Shah et al, 2020;Zhang et al, 2020a;. In some cases, rigidifying the linker through heterocyclic scaffolds (e.g., piperazine/piperidines) led to a stable ternary complex formation and potent protein degradation (Farnaby et al, 2019;Han et al, 2019).…”
Section: Challenges In Expanding the E3 Ligase Toolbox In Targeted Protein Degradationmentioning
confidence: 99%
“…This well-known "hook effect" negatively impacts PROTAC's potency in a concentrationdependent manner (Figure 3). Being an intrinsic event in PROTAC pharmacology, the hook effect is difficult to avoid and often occurs at concentrations in the range of 1-10 ”M, which are typically applied to test small molecules in vitro (Chan et al, 2018;Olson et al, 2018;Anderson et al, 2020;Shah et al, 2020;Yang et al, 2020;Zhang et al, 2020b,c;. Since positive cooperativity favors stable ternary complexes rather than unproductive binary complexes, it is reasonable to assume that the hook effect may be circumvented or at least reduced by improving cooperativebinding PPIs (Figure 3) (Gadd et al, 2017;Roy et al, 2017;Buhimschi et al, 2018).…”
Section: Ternary Complex Formation and Cooperativitymentioning
confidence: 99%
“…Nunes et al reported a VHL-based PROTAC that was capable of degrading IRAK4 in peripheral blood mononuclear cells and dermal fibroblasts with DC 50 values of 151 nM and 36 nM, respectively [ 184 ]. In addition, PROTACs targeting tripartite motif-containing protein 24 (TRIM24), receptor-interacting protein kinase 2 (RIPK2), and the Janus kinase family enzymes for degradation may also have the potential to be used to treat certain types of hematologic malignancies but require further studies [ 185 – 187 ].…”
Section: Protacs Against Hematologic Malignanciesmentioning
confidence: 99%